Simplicia and Extracts Standardization from Jualing Leaves (Micromelum minutum Wight & Arn.) from South Kalimantan - Sutomo Sutomo; Herwina Dita Lestari; Arnida Arnida; Agung Sriyono (Borneo Journal of Pharmacy, 2019)
Jualing (Micromelum minutum Wight & Arn.) is a plant from South Kalimantan that has the potential to be developed as natural medicine. This study aims to establish standardization which includes specific and non-specific parameters of M. minutum leaf simplicia and extracts from three growing locations, namely Banua Botanical Garden, Sultan Adam Forest Park, and Forest Areas with Specific Objects of Rantau, South Kalimantan. The method of setting standardization parameters refers to the Indonesian Herbal Pharmacopoeia and General Standard Extracts Parameters. Organoleptic standardization of simplicia is brownish-green, has a distinctive odor, has a bitter and slightly spicy taste. Microscopic observations showed the presence of stomata, cell walls, cytoplasm, calcium oxalate crystals, upper epidermis, palisade tissue, spongy tissue, cortex, xylem, phloem, lower epidermis, and trichomes. Water content test showed the results of 21.9-22.07%; ethanol extract content of 12.87-13.17%; drying losses 4.64-4.84%; total ash content of 6.04-6.14%; acid insoluble ash content 1.13-1.19%; Pb levels of 0.022-0.025 mg/kg; Cd levels of 0.017-0.020 mg/kg; and Hg levels <0.0004 mg/kg. Extract standardization shows thick green-black, thick-smelling extract and bitter taste. Micromelum minutum leaves contain alkaloids, flavonoids, saponins, terpenoids, tannins, anthraquinones, phenols, and glycosides. Thin Layer Chromatography profiles show the similarity of chemical compounds in each growth location. Other parameters are extract yield of 8.08-8.32%; moisture content of 6.07-6.27%; total ash content of 4.22-4.27%; and acid insoluble ash content 1.11-1.12%. All standardization parameters meet the requirements in the Media Materia Indonesia and the Republic of Indonesia Drug and Food Control Center.